EFEK LEVETIRACETAM DAN PENAMBAHAN FENITOIN PADA KEJADIAN KEJANG PASCAKRANIOTOMI TUMOR DI RSUPN Dr CIPTO MANGUNKUSUMO STUDI PENDAHULUAN - Astri Budikayanti, Meidianie Camellia, Tiara Aninditha, Setyo Widi Nugroho, Joedo Prihartono, Fitri (NEURONA, 2013)
INTRODUCTION LEVETIRACETAM IS THE DRUG OF CHOICE FOR SEIZURE IN BRAIN TUMOR PATIENTS IN CIPTO MANGUNKUSUMO HOSPITAL DUE TO ITS EFFECTIVENESS FAST ONSET LACK OF SIDE EFFECTS AND DRUG INTERACTIONS PHENYTOIN IS COMMONLY GIVEN TO BRAIN TUMOR PATIENTS TO CONTROL POSTOPERATIVE SEIZURE BECAUSE IT HAS INJECTION FORMULA AND EASY TO USE BUT HAS A SIGNIFICANT INTERACTION WITH STEROID AN ANTIEDEMA FOR BRAIN THE BENEFICIAL OF ADDING PHENYTOIN TO LEVETIRACETAM THERAPY HAS NEVER BEEN STUDIED BEFORE